Local sport club structures and their effect on athletic performance: The relationship between formalization and athletic performance in swimming - Wharam, D.; Geringer, S.; King, R.; Kerr, M. (The Sport Journal, 2020)
The purpose of this study applies an organizational structure perspective to athletic performance in competitive swimming in the United States. This research examines via survey the top USA Swimming clubs in the country as defined by their Club Excellence Program ranking. The Club Excellence Program is a voluntary program administered by USA Swimming that ranks teams based on the achievements of their elite 18 years and younger performers. The research focused on collecting contextual variables and structural variables relating to formalization. The relationship between the level of club formalization and elite athletic performance was examined.